Aspek Syariah dan Halal : Definisi, Etika Bisnis, Ciri Khas Bisnis, Akad, Kerjasama, dan Standar Operasional Prosedur Halal - Muhammad Alwi Hasibuan; Abdul Rahmad Rayadi; Ditia Azzahra Aswin Tanjung (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze and understand the principles of Sharia in business practices, especially in the context of sharia business which is growing rapidly in society. Using qualitative methods and a library approach, data were collected from various literature sources, including books, journals, and scientific articles. The main focus of the study includes the definition of Sharia, business ethics in Islam, contracts in transactions, and the implementation of halal Standard Operating Procedures (SOP). The results of the analysis show that sharia business is not only profit-oriented, but also prioritizes justice, honesty, and social responsibility in accordance with Islamic teachings. The principle of halal is an important foundation in creating consumer trust and improving product quality. This study makes a significant contribution to the development of theoretical and practical understanding of sharia business, and offers guidance for business actors to apply sharia principles in their operations, so as to create an ethical and sustainable business environment.